Drug–Drug Interactions and Phenytoin Therapeutic Response: A Systematic Literature Review - Suharjono Suharjono; Imamatus Shaleha; Findari Megantari; Lenny Octaviana; Putra Adi Purnama (Jurnal Ners, 2026)
Phenytoin is an antiepileptic drug with a narrow therapeutic window that is susceptible to drug interactions and other non-genetic factors, causing significant variability in therapeutic response among epilepsy patients. This systematic review aims to examine types of drug interactions affecting pharmacokinetics and pharmacodynamics of phenytoin, analyze their impact on therapeutic effectiveness and toxicity, and present the role of non-genetic factors in response variability as a basis for individualized therapy. Literature search was conducted using PRISMA framework across PubMed, Scopus, Web of Science, Science Direct, and Cochrane Library databases from 2015-2024, yielding 10 articles meeting inclusion criteria. Review findings indicated that 66 percent of patients experienced drug interactions with pharmacokinetic predominance reaching 81.4 percent, involving omeprazole, amlodipine, and aspirin as the most frequently interacting agents. Polytherapy doubled the risk of poor seizure control, while therapy duration exceeding one year correlated with executive function impairment. Interactions with herbal products such as noni reduced plasma levels to subtherapeutic ranges. Non-genetic factors, particularly drug interactions, contribute substantially to phenytoin response variability, making individualized therapy based on therapeutic drug monitoring and comprehensive evaluation of patient medication profiles essential for optimizing therapy safety and effectiveness